Pengaruh Load Balancing Pada Pemrosesan Paralel untuk Kompresi Video - ., Sudaryanto; Adji, Teguh Bharata; Nugroho, Hanung Adi (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Communication and multimedia, especially video data processing require very high resource both computing resources and communication traffic. This requires high-end machines such as servers with high specifications are of course very expensive. This results builds a web based application that implements the concept of parallel processing with load balancing process based CPU Usage to compress video files with FFmpeg software.The results are conditioned compression has half the resolution of the original video data. Based on the test results indicate with load balancing process parallel concepts used, the compression process showed an average speed up value of 8.07% faster than paralle Non load balancing process with 2 compressors, 37.57% with 3 compressors, and 41.24% with 4 compressors. The level of processor efficiency by 28.76% more efficient than paralle Non load balancing process with 2 compressors, 37.57% with 3 compressor, and 41.24% with 4 compressors. Keywords: pemrosesan paralel, kompresi video, Load Balancing, CPU Usage